The Use of Pulsed Modes in the Electrochemical Polishing of Corrosion-Resistant Steels - Yu. G. Aliakseyeu; A. Yu. Korolyov; V. S. Niss; A. E. Parshuto; A. S. Budnitskiy (Наука и техника)
However, the ECP in its classical form has a number of significant drawbacks. One of them is a dependence of treatment modes and electrolyte compositions on the processed material. In addition, aggressive expensive electrolytes that require special technologies for disposal are used for ECP. Electrolytes in ECP often require heating to a temperature of 60–90 °C. Processing at such temperatures causes significant harm to the environment and production personnel. To eliminate the existing disadvantages of the ECP and expand its technological capabilities, a processing method with application of pulsed unipolar and bipolar modes has been proposed. As a result, fundamentally new processes of pulse ECP with a pulse duration of 0.05–20.00 ms have been developed. They provide a reduction of energy costs for the process and high efficiency of polishing in comparison with traditional DC polishing. The rate of smoothing micro-roughness of the treated surface related to the total metal removal is significantly increased. The use of pulse modes in comparison with traditional ECP allows processing in universal electrolytes of simple compositions based on sulfuric and orthophosphoric acids without addition of chromium anhydride. Application of the developed pulse modes, which will provide at low metal removal a significant change in surface roughness, is the most appropriate for the ECP of precise parts, products or parts of small cross-section and rigidity, such as medical devices for minimally invasive surgery, precision engineering parts, etc. The paper presents results of a study for influence of pulsed unipolar and bipolar ECP modes on the surface quality of stainless steel specimens, as well as a comparative analysis of the efficiency of using pulsed ECP modes instead of DC polishing. The technological parameters of ECP using pulsed modes, providing the highest quality surface polishing with high efficiency of micro-roughness smoothing and low energy consumption have been established in the paper.